The assistance of Village-Owned Enterprises (BUMDes) as a support of the Jembayan Tengah tourism village - Eman Sukmana; M. Fauzan Noor; I Wayan Lanang Nala; Bhanu Rizfa Hakim; Rizky Sulvika Puspa Rinda; Anton Nurcahyo (Universitas Muhammadiyah Magelang, 2021)
Preparation of Jembayan Tengah Village towards an agro-tourism area based on agriculture and a creative economy is one of the priorities. BUMDes DJT Berjaya in collaboration with the Tourism Awareness Group (POKDARWIS) Kampong Seraong to create a sustainable Jembayan Tengah Tourism Village. In terms of organizational governance, BUMDes DJT Berjaya is in crisis, but this organization is open to restructuring management by the community who are committed to advancing the village. This service program is focused on BUMDes management training to improve the governance system and classify business units. In addition, training on the creation and management of village websites was carried out as a first step in digitizing which will work together with kutaicoding.com. The results are an increase in the quality of organizational governance for BUMDes and POKDARWIS as well as the creation of a website that contains profiles, organizational activities and complaint features.